2019
DOI: 10.3390/coatings9100637
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate-Bitumen Interface Enhancement Mechanism of Utilization of Oil Shale Waste as Fine Aggregate in Open Grade Friction Course

Abstract: Oil shale waste (OSW), as fine aggregate in the mixture (particle size less than 4.75 mm), can effectively improve the overall properties of open grade friction course (OGFC), but the reinforcement mechanism is not clear. Thus, a comprehensive investigation of the reinforcement mechanism of OSW as fine aggregate is essential to provide better understanding for promoting its engineering application. In this paper, the reinforcement mechanism of OSW was explored through numerical calculations and laboratory test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…It is obvious that the original simple circle cannot represent the actual shape of the aggregate. Hence, the aggregates with a complex shape and uniform distribution are used to form the virtual asphalt mixture specimen [30]. The gradation of the virtual asphalt mixture is consistent with the RSCT test.…”
Section: Basic Assumptionsmentioning
confidence: 56%
See 1 more Smart Citation
“…It is obvious that the original simple circle cannot represent the actual shape of the aggregate. Hence, the aggregates with a complex shape and uniform distribution are used to form the virtual asphalt mixture specimen [30]. The gradation of the virtual asphalt mixture is consistent with the RSCT test.…”
Section: Basic Assumptionsmentioning
confidence: 56%
“…Papagiannakis studied the plastic deformation behaviors of asphalt mixtures subjected to loading using DEM [27]. However, most existing studies consider the actual interface morphology of the mixture [28][29][30][31], and the corresponding virtual tests may only be used once. The relationship between the displacement of particles with different sizes and the macroscopic deformation has yet to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…After magnifying observation, it was found that the surface of oil shale waste is rough, that oil shale waste has a large number of micron-sized pores, and the edge of the pores is surrounded by mossy and petal-like protrusions. Such a unique microscopic appearance can achieve a larger bonding area when combined with asphalt, reduce the content of surplus asphalt, and effectively reshape the combination mode of asphalt and aggregate [37].…”
Section: Oil Shale Wastementioning
confidence: 99%
“…In a previous study, in order to determine a promising solution to minimize environmental pollution by sinking the accumulation of waste materials and improve the strength durability of permeable pavement, a novel OGFC material, named COF-OGFC, using oil shale waste as a fine aggregate in OGFC, was designed to meet the requirements of sponge city construction in Siping City (Jilin province, China). The test results showed that the overall properties of COF-OGFC were about 30% better than those of a conventional asphalt mixture, and it could effectively reduce construction costs and environmental pollution by industrial waste [37,38]. However, the permeability durability when using oil shale waste as a fine aggregate in OGFC in seasonal frozen regions is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Asphalt pavement is the most widely used advanced pavement in global pavement construction due to the special properties such as low noise, high comfort and strong repairability [1][2][3]. More than 94% of the 2.7 million miles of paved roads in the United States are surfaced with asphalt [4,5].…”
Section: Introductionmentioning
confidence: 99%